Pengaruh Corporate Image dan Competitive Advantages Terhadap Economics Performance - Dirvi Surya Abbas; Savera Wulan Pratiwi; Hesty Erviani Zulaccha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to determine the effect of corporate social responsibility, corporate image and competitive advantage on economic performance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The research time period used is 4 years, namely the 2018-2021 period. The population of this study includes all state-owned companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 10 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 9.0. The results of this study indicate that Corporate Social Responsibility and Corporate Image have no effect on Economics Performance, while Competitive Advantage has an effect on Economics Performance.